Validation of Forensic Expert’s Opinion in Investigation of Safety Rules Violations in Construction Works - A. E. Fomenko (Теория и практика судебной экспертизы)
The article aims to review the pressing issues of expert’s opinion validation in criminal cases related to investigation of safety rules violations in construction work and to find ways to resolve them. The following assessment criteria are addressed in the paper: expert’s qualification and competence, correctness of an expert’s opinion drafting, thoroughness and scientific validation of a research, coherence and correlation between findings and research part of an expert’s opinion, cogency of an opinion to an investigator (court) and other parties to the proceedings. Based on the expert practice analysis typical examples of problem situations related to validation of this type of expert’s opinions are given as well as the ways to resolve them are suggested and justified. The information presented may be of practical interest when preparing an evaluative judgement on an expert’s opinion on the category of cases in question.